A constitutive model coupling irradiation with two-phase lithiation for lithium-ion battery electrodes. Issue 8 (18th April 2019) - Wu, Hui; Xie, Zhoucan; Wang, Yan; Zhang, Panpan; Sun, Lizhong; Lu, Chunsheng; Ma, Zengsheng
ABSTRACT: When lithium-ion batteries serve in extreme environments like space, severe irradiation might induce significant decay of the electrochemical performances and mechanical properties. In this paper, an electrochemical-irradiated constitutive model is proposed to explore the evolution of dislocation, defect and stress in electrodes during a two-phase lithiation process. The results from the analytic formulation and finite difference calculations show that, as Li intercalation proceeding, the hoop stress in the surface of a spherical particle converts from compression into tension because the large lithiation strain and plastic yielding at the front pushes out the material behind it. And the plastic flow resistance continuously increases with increasing irradiation dose result from the impediment of a defect to dislocation glide. There is a clear peak in the distribution of stress at yielding locations due to the competition between dislocations multiplication and defects annihilation. The model is meaningful for thoroughly understanding the micro-mechanism of lithiation deformation and provides a guideline for predicting their mechanical behaviours of lithium-ion batteries in unconventional environment.